Analisis Kemampuan Pemahaman Konsep Siswa SMK Ditinjau Dari Kecemasan Matematis - Hermawan, Sony Elvianto; Zawawi, Irwani; Khikmiyah, Fatimatul (Universitas Muhammadiyah Gresik, 2024)
This research is motivated by the importance of concept understanding skills that must be possessed by every student. Concept understanding ability is a basic ability that must be possessed by every student because in learning mathematics to be able to proceed to new material students must understand the concept first. One of the factors that affect concept understanding ability is mathematical anxiety. The purpose of this study is to analyze and describe the concept understanding ability of vocational students in terms of mathematical anxiety. This type of research is descriptive research with a qualitative approach. This research was conducted at SMK Muhammadiyah 4 Sangkapura, with the research population being class X students with a total of 13 students in the 2023/2024 even semester. The data collection methods used were mathematical anxiety questionnaire, concept understanding ability test and interview. The questionnaire results were used to group students into categories of low, medium and high levels of mathematical anxiety, then select 3 students as research subjects. The results of the concept understanding ability test and interviews were then analyzed based on the level of mathematical anxiety. The results showed that students with low levels of mathematical anxiety were able to fulfill all indicators 1 to 6, then students with moderate levels of mathematical anxiety were able to fulfill 5 indicators, namely indicators 1, 2, 3, 5 and 6. While students with high levels of mathematical anxiety were only able to fulfill 2 indicators, namely indicators 1 and 2.